Food addiction: a valid concept? - Fletcher, Paul C.; Kenny, Paul J. (Neuropsychopharmacology (New York, N.Y.), 2018)
Can food be addictive? What does it mean to be a food addict? Do common underlying neurobiological mechanisms contribute to drug and food addiction? These vexing questions have been the subject of considerable interest and debate in recent years, driven in large part by the major health concerns associated with dramatically increasing body weights and rates of obesity in the United States, Europe, and other regions with developed economies. No clear consensus has yet emerged on the validity of the concept of food addiction and whether some individuals who struggle to control their food intake can be considered food addicts. Some, including Fletcher, have argued that the concept of food addiction is unsupported, as many of the defining features of drug addiction are not seen in the context of feeding behaviors. Others, Kenny included, have argued that food and drug addiction share similar features that may reflect common underlying neural mechanisms. Here, Fletcher and Kenny argue the merits of these opposing positions on the concept of food addiction.